TINJAUAN SISTEMATIS PRISMA - Bayu Rizqi; Masita Dwi Mandini Manessa (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2025)
Food is a basic human need and a fundamental right for every individual, with rice serving as one of the primary carbohydrate sources for more than half of the world's population. However, population growth and shifts in human values have led to the conversion of rice fields into urban areas, significantly impacting rice production and global rice availability. This literature review employed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method to conduct a systematic review of relevant literature. Out of an initial total of 186 articles retrieved, 38 articles met the criteria for in-depth analysis. The analysis revealed that research on land-use changes over the past decade tended to discuss the conversion of rice fields separately from aspects of rice self-sufficiency. However, these two issues were interconnected and shared a deep relationship. The conversion of rice fields continued to occur massively and often uncontrollably across nearly all regions of the world, potentially threatening the balance of rice availability in the future. Through this literature review, the authors aimed to integrate various perspectives to illustrate the causal relationship between the carrying capacity of rice fields and efforts toward food self-sufficiency. As an agrarian nation, policies promoting regional rice self-sufficiency could be considered as an alternative approach to achieving future food security standards, based on the principle that each region should be able to meet its rice needs independently. Therefore, in-depth analysis is necessary to formulate appropriate strategies so that land-use changes remain well-monitored while future food needs are guaranteed.